2022
DOI: 10.1038/s41598-022-21590-w
|View full text |Cite
|
Sign up to set email alerts
|

Thermo-optic tuning of silicon nitride microring resonators with low loss non-volatile $$\hbox {Sb}_{2}\hbox {S}_{3}$$ phase change material

Abstract: A new family of phase change material based on antimony has recently been explored for applications in near-IR tunable photonics due to its wide bandgap, manifested as broadband transparency from visible to NIR wavelengths. Here, we characterize $$\hbox {Sb}_{2} \hbox {S}_{3}$$ Sb 2 S 3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 74 publications
(72 reference statements)
0
3
0
Order By: Relevance
“…The work demonstrates the low insertion loss and non-volatile building block waveguide platform for more complex photonic integrated circuit (PIC) architectures and applications. Other important works using novel PCM such as Sb 2 S 3 and Sb 2 Se 3 on ring resonators and directional couplers include (see figures 3(E)-(J)) [16,91,92,94,95].…”
Section: Loading On Conventional Microphotonic Componentswaveguides A...mentioning
confidence: 99%
See 1 more Smart Citation
“…The work demonstrates the low insertion loss and non-volatile building block waveguide platform for more complex photonic integrated circuit (PIC) architectures and applications. Other important works using novel PCM such as Sb 2 S 3 and Sb 2 Se 3 on ring resonators and directional couplers include (see figures 3(E)-(J)) [16,91,92,94,95].…”
Section: Loading On Conventional Microphotonic Componentswaveguides A...mentioning
confidence: 99%
“…Ilie et al [92] demonstrated high extinction ratio (> 20 dB) and 1.92 nm FSR using <50 um long low-loss Sb 2 S 3 . The device operating in the 1550 nm window showed bi-directional wavelength shifting capabilities with effective refractive index modulation ranging from +5.23 × 10 −5 to −1.20 × 10 −4 using a CW laser at 1550 nm.…”
Section: Loading On Conventional Microphotonic Componentswaveguides A...mentioning
confidence: 99%
“…Brain-inspired computing [ 1 , 2 , 3 ], light-controlled (i.e., over a wide spectral range, from visible to THz) or electrically controlled reconfigurable optical metamaterials [ 4 , 5 , 6 ], high resolution holographic and nonvolatile displays [ 7 , 8 ], integrated photonic circuits [ 9 , 10 ], and many other applications need next-generation phase-change materials (PCMs) with better energy efficiency and wider temperature and spectral ranges to increase reliability compared to current flagship PCMs, such as Ge 2 Sb 2 Te 5 , doped Sb 2 Te, etc. Gallium tellurides seem to be promising candidates to achieve the necessary requirements because of their higher melting and crystallization temperatures, combined with low switching power and fast switching rate [ 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%